2015
DOI: 10.3390/life5010102
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose in Cyanobacteria: From a Salt-Response Molecule to Play a Key Role in Nitrogen Fixation

Abstract: In the biosphere, sucrose is mainly synthesized in oxygenic photosynthetic organisms, such as cyanobacteria, green algae and land plants, as part of the carbon dioxide assimilation pathway. Even though its central position in the functional biology of plants is well documented, much less is known about the role of sucrose in cyanobacteria. In those prokaryotes, sucrose accumulation has been associated with salt acclimation, and considered as a compatible solute in low-salt tolerant strains. In the last years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 71 publications
(130 reference statements)
2
58
0
Order By: Relevance
“…Respiration in the heterocysts requires a source of reductant that is received from the adjacent vegetative cells. In Anabaena , sucrose appears to be the main source of intercellularly transferred reductant, since inactivation of an invertase, InvB, expressed specifically in the heterocysts blocks diazotrophic growth (López‐Igual et al ., ; Vargas et al ., ; reviewed in Kolman et al ., ). Invertases irreversibly cleave sucrose into glucose and fructose, and the oxidative pentose phosphate pathway mediates sugar catabolism in the heterocysts (Summers et al ., ).…”
Section: N2 Fixation and The Heterocystmentioning
confidence: 97%
“…Respiration in the heterocysts requires a source of reductant that is received from the adjacent vegetative cells. In Anabaena , sucrose appears to be the main source of intercellularly transferred reductant, since inactivation of an invertase, InvB, expressed specifically in the heterocysts blocks diazotrophic growth (López‐Igual et al ., ; Vargas et al ., ; reviewed in Kolman et al ., ). Invertases irreversibly cleave sucrose into glucose and fructose, and the oxidative pentose phosphate pathway mediates sugar catabolism in the heterocysts (Summers et al ., ).…”
Section: N2 Fixation and The Heterocystmentioning
confidence: 97%
“…The evolutionary origin of enzymes from sucrose metabolism in proteobacteria has been previously discussed (4,5,8,64). The evolution of sucrose synthases in cyanobacteria, proteobacteria, and plants is not yet fully understood, but most likely it involved horizontal gene transfers.…”
Section: Ii) Sugar-binding Gt-b(a) Domainmentioning
confidence: 99%
“…In the present study, 70 proteins associated with carbohydrate metabolism have been identified in the three strains. Sucrose plays a critical role in carbon flux modulation in the nitrogen‐fixing filaments of Anabaena . Sucrose biosynthesis can be performed both in vegetative cells and heterocysts .…”
Section: Resultsmentioning
confidence: 99%